2012
DOI: 10.1111/j.1467-8551.2012.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minority Women in the Scottish Labour Market: Employers' Perceptions

Abstract: This paper contributes to an under-researched area through investigating employers' perceptions of ethnic minority women in the Scottish labour market. Adopting a social constructionist approach which acknowledges agency and structure and incorporates insights relating to organizational and social group culture, the study highlights the influence of individual (micro), organizational (meso) and contextual (macro) factors on ethnic minority women's participation in the labour market. The paper is based on quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…Similarly, a study by Hutchings et al (2010) of Arab Middle Eastern women working on international assignments found that non-Muslim countries' citizens were prejudiced against female Arabian (that is generally Muslim women), who had more difficulty in coping with aggressive work environments. Kamenou, Netto, and Fearfull (2013) found that organisational commitment to equal employment opportunities in the Scottish labour market is questionable and that there is low awareness on the unique socio-cultural position of ethnic minority women. Similarly, Syed and Pio (2010: p. 130) found in a study of Muslim migrant women in Australia that given multi-level frameworks of diversity e.g., at the macro-societal, meso-organisational and micro-individual, policy planners should be cognisant of ethnic and religious bargains and the context from which these are formed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study by Hutchings et al (2010) of Arab Middle Eastern women working on international assignments found that non-Muslim countries' citizens were prejudiced against female Arabian (that is generally Muslim women), who had more difficulty in coping with aggressive work environments. Kamenou, Netto, and Fearfull (2013) found that organisational commitment to equal employment opportunities in the Scottish labour market is questionable and that there is low awareness on the unique socio-cultural position of ethnic minority women. Similarly, Syed and Pio (2010: p. 130) found in a study of Muslim migrant women in Australia that given multi-level frameworks of diversity e.g., at the macro-societal, meso-organisational and micro-individual, policy planners should be cognisant of ethnic and religious bargains and the context from which these are formed.…”
Section: Introductionmentioning
confidence: 99%
“…Kamenou and Fearfull, 2006;Ogbonna and Harris, 2006) or at institutional/organizational level (see Kamenou et al, 2013;McGinnity and Lunn, 2011), with limited attention paid to the interactions and combined impacts across the levels. Through incorporating the managerial and organizational context, this study finds that what is seemingly discrimination at a single level of individuals and groups reveals more sinister managerial and organizational level discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by the passage of the Civil Rights/Equality Acts in the United States and Europe, earlier research (1960s–1980s) focused mainly on the extent of discrimination in the human resource functions, such as recruitment and selection, training and development, performance appraisal and rewards (Shore et al, ). There has also been considerable research in differences between ethnic and racial groups in terms of job satisfaction, commitment, motivation, leadership, and performance (Kamenou, Netto, & Fearfull, ; McKay & McDaniel, ; Williams & O'Reilly, ). By the 1990s, research on this dimension of diversity began to focus on work teams and the business case for managing an increasingly diverse workforce (S. E. Jackson, Joshi, & Erhardt, ; Mannix & Neale, ).…”
Section: Key Themes In the Field Of Diversity And Inclusion Managementmentioning
confidence: 99%